2017
DOI: 10.18632/genesandcancer.126
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against oncogenic ERG protein in prostate cancer: potential use in diagnosis and prognosis in a panel with C-MYC, AMACR and HERV-K Gag

Abstract: Overdiagnosis and overtreatment of prostate cancer (CaP) is attributable to widespread reliance on PSA screening in the US. This has prompted us and others to search for improved biomarkers for CaP, to facilitate early detection and disease stratification. In this regard, autoantibodies (AAbs) against tumor antigens could serve as potential candidates for diagnosis and prognosis of CaP. Towards this, our goals were: i) To investigate whether AAbs against ERG oncoprotein (overexpressed in 25-50% of Caucasian Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 106 publications
1
10
0
Order By: Relevance
“…A number of studies have shown that autoantibodies can have low titers in tumorigenesis. These autoantibodies, targeting carcinoma antigen, could have an effect on receptors of carcinoma cells, thereby stopping cell proliferation [21,22]. They come into being in the early stage of carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that autoantibodies can have low titers in tumorigenesis. These autoantibodies, targeting carcinoma antigen, could have an effect on receptors of carcinoma cells, thereby stopping cell proliferation [21,22]. They come into being in the early stage of carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, anti-HERV-K Gag and Env antibodies were negatively related to disease-specific overall survival, suggesting that humoral anti-HERV-K immune response may provide additional prognostic information to that of established melanoma markers (Hahn et al, 2008). Autoantibodies against HERV-K Gag together with ERG and AMACR may be a useful panel of biomarkers for diagnosis and prognosis of prostate cancer (Rastogi et al, 2016). Anti-HERV-K antibodies were detected in patients with ovarian cancer, but not in normal female controls, documenting that HERV Env proteins, especially those expressed on the cell surface, may serve as novel tumor targets for detection, diagnosis, and immunotherapy of ovarian cancer (Wang-Johanning et al, 2007).…”
Section: Humoral and Cellular Immune Response To Herv-k (Hml-2) Proteinsmentioning
confidence: 99%
“…Both anti-HERV antibodies and HERV mRNA have been reported as biomarkers for prostate cancer and antibody production has been discussed as potential cancer immunotherapy [ 118 , 119 , 123 , 124 , 125 , 126 ]. HERV-K gag mRNA expression in prostate cells is regulated by both HERV promoter demethylation and androgen stimulation [ 117 ].…”
Section: Herv-k In Cancer Immunotherapymentioning
confidence: 99%
“…A panel for the detection of autoantibodies, including those against HERV and three host proteins, has been tested for analyzing the potential of using these autoantibodies in the diagnosis of prostate cancer [ 119 ]. The results showed that the detection of the anti HERV-K Gag antibody along with other host antibodies was successful in differentiating cancer patients from healthy subjects [ 119 ].…”
Section: Herv-k In Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation